1983
DOI: 10.1159/000287744
|View full text |Cite
|
Sign up to set email alerts
|

Adherence by Medical-Surgical Inpatients to Recommendations for Outpatient Psychiatric Treatment

Abstract: A records review of medical-surgical inpatients at a university hospital reveals that only 20 % of patients seen in psychiatric consultation followed recommendations to seek psychiatric outpatient treatment. The study is unique in that immediate appointments with the consulting psychiatrists were offered prior to patients’ discharge. The low rate is similar to the findings by others. Diagnosis of depression was associated with patients agreeing to psychiatric treatment. Race was significantly associated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Our study found a greater degree of post-hospitalization psychiatric aftercare follow-up (57%) than did the study by Weddington (20%) [5], but a similar rate to that found by Burstein (51%) [6]. Unlike Weddington's study, our study found no racial differences with respect to follow-up.…”
Section: Discussionsupporting
confidence: 67%
“…Our study found a greater degree of post-hospitalization psychiatric aftercare follow-up (57%) than did the study by Weddington (20%) [5], but a similar rate to that found by Burstein (51%) [6]. Unlike Weddington's study, our study found no racial differences with respect to follow-up.…”
Section: Discussionsupporting
confidence: 67%
“…The majority of primary care patients express interest in nonsomatic treatments prior to or in combination with antidepressant care [84,[88][89][90][91][92][93]. Mohr et al (2006) confirmed previous findings that although patients said they would prefer psychotherapy, less than 20% actually followed-up [92,94] and half dropped out of treatment [88,95]. BOX 4 illustrates the barriers to psychotherapy found in psychotherapy access research.…”
Section: S63supporting
confidence: 65%
“…For example, up to two thirds of depressed primary care patients would prefer psychological treatments to pharmacotherapy (Bedi et al, 2000; Brody, Khaliq, & Thompson, 1997; Churchill et al, 2000; Dwight-Johnson, Sherbourne, Liao, & Wells, 2000; O’Mahen & Flynn, 2008; Priest, Vize, Roberts, Roberts, & Tylee, 1996). However, in spite of the desirability of such services, only around 20% of patients referred for psychological treatments ever enter treatment (Brody et al, 1997; Weddington, 1983), and of those, nearly half drop out before completion (Wierzbicki & Pekarik, 1993). Such large inconsistencies between stated interest and actual follow-up suggest that substantial barriers both to initiating and to adhering to psychological interventions exist (Hollon et al, 2002; Wells et al, 2002).…”
mentioning
confidence: 99%